1990
DOI: 10.1093/bja/64.4.524
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Barotrauma Associated With Transtracheal Jet Ventilation

Abstract: Two patients suffered barotrauma whilst undergoing transtracheal jet ventilation (TTJV). In the first, TTJV was provided by a Sanders injector and in the second it was given by a high frequency jet ventilator. Barotrauma was a consequence of the expiratory pathway becoming blocked. The mechanism of barotrauma and a method of airway pressure monitoring during TTJV are discussed. It is recommended that meticulous care is taken to ensure an adequate path for expiration when jet ventilation is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 12 publications
1
34
0
2
Order By: Relevance
“…Upper airway obstruction is usually associated with anatomical, functional or pathological supraglottic lesions [3] such as epiglottitis, tumours, oedema and trauma. During ENT surgery, obstruction secondary to blood and tumour debris has also been reported [6]. In our experience, in patients with a normal anatomy, the tongue is usually the cause of obstruction, because of displacement towards the posterior pharyngeal wall.…”
Section: Discussionmentioning
confidence: 64%
“…Upper airway obstruction is usually associated with anatomical, functional or pathological supraglottic lesions [3] such as epiglottitis, tumours, oedema and trauma. During ENT surgery, obstruction secondary to blood and tumour debris has also been reported [6]. In our experience, in patients with a normal anatomy, the tongue is usually the cause of obstruction, because of displacement towards the posterior pharyngeal wall.…”
Section: Discussionmentioning
confidence: 64%
“…In this instance, the conditions for the problem were initially established by use of an improvised oxygen delivery system. We note a previous report of barotrauma in a premature infant caused by attaching high-pressure tubing directly to an ETT (rather than a nasal cannula for "blow-by" oxygen as intended) [4], and during jet ventilation when expiratory outflow was obstructed [5]. Failed needle decompression of tension pneumothorax due to inadequate needle length also has been reported, and imaging studies of chest wall thickness at the second intercostal space in the midclavicular line have shown that a needle longer than 5 cm (maximum 8.2 cm) is needed to reach the pleural space in a substantial number of patients [6,7].…”
Section: Discussionmentioning
confidence: 84%
“…The major disadvantage of jet ventilation, especially in cases involving a partially or completely obstructed upper airway, is the potential for barotrauma (subcutaneous emphysema or pneumothorax) if exhalation is inadequate and airway pressure is elevated 14. In addition, monitoring of CO 2 elimination during jet ventilation can only be performed by means of blood-gas measurement.…”
Section: Discussionmentioning
confidence: 99%